2015
DOI: 10.5614/j.math.fund.sci.2015.47.3.6
|View full text |Cite
|
Sign up to set email alerts
|

On The Total Irregularity Strength of Regular Graphs

Abstract: Abstract. Let = ( , ) be a graph. A total labeling : ∪ → {1, 2, ⋯ , } is called a totally irregular total -labeling of if every two distinct vertices and in satisfy ( ) ≠ ( ) and every two distinct edges 1 2 and 1 2 in satisfyThe minimum for which a graph has a totally irregular total -labeling is called the total irregularity strength of , denoted by ( ). In this paper, we consider an upper bound on the total irregularity strength of copies of a regular graph. Besides that, we give a dual labeling of a totall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…By Equations ( 7), ( 8), (9), and Theorem 2.1, we can conclude that complete bipartite graph K m,n for any positive integer m and n is a totally irregular total graph with , otherwise.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…By Equations ( 7), ( 8), (9), and Theorem 2.1, we can conclude that complete bipartite graph K m,n for any positive integer m and n is a totally irregular total graph with , otherwise.…”
Section: Discussionmentioning
confidence: 92%
“…For several cartesian product graphs, Ramdani and Salman in [8], showed that the lower bound (6) is sharp. Later, Ramdani, Salman, and Assiyatun [9] gave an upper bound of ts for some regular graphs. Then, in [10], Ramdani, Salman, Assiyatun, Semaničová-Feňovčíková, and Bača, proved that gear graphs, fungus graphs, ts(F g n ), for n even, n ≥ 6; and disjoint union of stars are totally irregular total graphs with the ts equal to their tes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], Ramdani et al determined the total irregularity strength of regular graphs. In the paper, they gave an upper bound on total irregularity strength of copies of arbitrary graph .…”
Section: Introductionmentioning
confidence: 99%
“…In [21] there are given upper and lower bounds for the parameter ts(G). Ramdani and Salman in [24] determined the exact values of the total irregularity strength for several Cartesian product graphs.…”
Section: Introductionmentioning
confidence: 99%